Biopotential acquisition unit for energy‐efficient wearable health monitoring. Issue 2 (30th May 2018) - Singh, Wazir; Deb, Sujay
Abstract : In wearable health monitoring system, the energy consumption is dominated by the transmitter. These systems generally use proprietary acquisition platforms that are incompatible with each other which makes this even more challenging. This study presents a compressive sensing‐based biopotential acquisition unit to reduce the overheads of wirelessly transmitting and storing the data. The instrumentation amplifier (INA) in the system defines the quality of the acquired biopotential signals. At the heart of the system is an analogue‐to‐information converter (AIC) to enable the random under‐sampling operation. AIC is used to digitise the output of the biopotential INA. Both INA and AIC are implemented in 65 nm CMOS technology. To confirm stable operation under different operating conditions, the design is simulated under different process, voltage and temperature (PVT) corners. The simulation results show that the proposed INA has a common mode rejection ratio of 100.18 dB and noise of 35.89 pV/sqrt (Hz). AIC achieves a sampling rate of 0.5 kS/s, an effective number of bits 9.54 bits, figure of merit 187 fj/conv‐step, and consumes 69.33 nW from 1 V power supply.